Impact of Medical Community Model on Intravenous Alteplase Door-to-Needle Times and Prognosis of Patients With Acute Ischemic Stroke - Li, Hongfei; Xu, Dongjuan; Xu, Yunyun; Wei, Lianyan (Frontiers in Surgery, 2022)
Objective: In this study, we retrospectively analyzed 795 AIS patients who received intravenous alteplase for thrombolytic therapy in one third-class hospital or three second-class hospitals in Dongyang City and sought to evaluate the effects of medical community model on intravenous alteplase door-to-needle time (DNT) and prognosis of patients with acute ischemic stroke. Methods: According to whether the medical community model is established or not, 303 AIS patients (204 cases from the third-class hospital and 99 cases from three second-class hospitals) were assigned into control group unavailable to the medical community model and 492 AIS patients (297 cases from the third-class hospital and 195 cases from three second-class hospitals) into observational group available to the medical community model. Results: A higher thrombolysis rate, a shorter DNT, more patients with DNT ≤ 60 min and DNT ≤ 45 min, a shorter ONT, lower National Institutes of Health Stroke Scale (NIHSS) scores at 24 h, 7 d, 14 d, and modified Rankin scale (mRS) scores at 3 months after thrombolytic therapy, a shorter length of hospital stay, and less hospitalization expense were found in the observational group than the control group. Subgroup analysis based on different-class hospitals revealed that the medical community model could reduce the DNT and ONT to increase the thrombolysis rate of AIS patients, especially for low-class hospitals. After establishment of medical community model, the AIS patients whether from the third-class hospital or three second-class hospitals exhibited lower NIHSS scores at 24 h, 7 d, 14 d after thrombolytic therapy (p < 0.05). After 90-day follow-up for mRS scores, a significant difference only noted in the mRS scores of AIS patients from the third-class hospital after establishing medical community model (p < 0.05). It was also found that the medical community model led to reduced length of hospital stay and hospitalization expense of AIS patients, especially for the second-class hospitals. Conclusion: The data suggest that medical community model could significant reduce intravenous alteplase DNT and improve the prognosis of patients with AIS.